Gender Relations in Islamic Inheritance Law: A Comparative Study of Sunni and Shia Perspectives - Zuhrah Zuhrah; Husnatul Mahmudah; Nurfitriani (Bulletin of Community Engagement, 2026)
This study compared the Sunni and Ja'fari Shia approaches to the gender-based distribution of inheritance rights in Islamic law. The Sunni school generally maintained a literal interpretation of Qur'anic provisions, particularly Surah al-Nisāʾ verses 11 and 176, which prescribed a 2:1 inheritance ratio between male and female heirs and tended to reinforce a patriarchal legal structure. In contrast, the Jaʿfari Shia school placed greater emphasis on ijtihād and maqāṣid al-sharīʿah, thereby allowing a more adaptive and context-sensitive distribution of inheritance, particularly in relation to women's economic roles. This research examined the differences in gender perspectives within Islamic inheritance law as developed by the Sunni and Ja'fari Shia schools and analyzed their implications for justice. The issue was particularly significant because the Sunni system distinguished inheritance shares between sons and daughters, whereas the Jaʿfari system promoted a more bilateral principle in which gender positions within the line of inheritance carried almost equivalent legal weight, although inheritance ratios remained grounded in Qur'anic texts. This study employed a normative juridical approach based on library research, drawing on classical fiqh texts, interpretations of inherited verses, school-based legal literature, and empirical findings from scholarly journals published over the past decade. The findings indicated that the Sunni school tended to maintain a textual-literal approach that ensured legal certainty but was less responsive to changes in women's socio-economic roles. By contrast, the Jaʿfari Shia school developed a more contextual framework grounded in maqāṣid al-sharīʿah and maṣlaḥah, which allowed inheritance distribution to become more responsive and equitable. The novelty of this study lay in the formulation of a trans-madhhab analytical model that integrated normative inheritance law with the social realities of family life and proposed a framework for the reform of Islamic inheritance law that emphasized substantive justice and gender equality without ignoring the legitimacy of scriptural sources.